EVALUATION OF ELEUTHERINE (ELEUTHERINE AMERICANA) POTENTIAL AS FEED ADDITIVE FOR POULTRY - Rusdi, Rusdi; Hasanuddin, Asriani; Arief, Rosmiaty (AgriSains, 2016)
In vitro studies were exploring eleutherine (Eleutherine americana) potential to be used as feed additive for poultry.Â  The eleutherine bulbs were extracted using four different organic solvents: methanol, ethyl acetate, diethyl ether and hexane.Â  The crude extracts were analyzed for their bioactive compounds, tested for anioxidant and antibacterial activity and tested for growth of non-pathogen bacteria. The results indicated that bioactives are indentified:phenol and tannin. Average of antioxidant activity were 33.74, 20.36, 15.14 and 1.98 ppm AEACÂ  for methanol, ethylacetate, diethylether and hexane, respectively. Furthermore, average of inhibition growth forÂ  pathogen bacteria of Escherichia coli was 5.94, 4.75, 4.56 and 4.44Â  mmÂ  forÂ  methanol, ethylacetate, diethylether and hexane, respectively, while inhibition forÂ  Staphylococcus aureus was 5.37, 6.50, 5.37 and 5.18Â  mm forÂ  methanol, ethylacetate, diethylether and hexane, respectively. The extracts also have ability to enhance the gorwth of non-pathogen bacteria Lactobacillus acidophilus. Average of bacteria growth improvement was 21.12, 28.57, 28.16 and 19.59 NTU for methanol, ethylacetate, diethylether and hexane, respectively. The presence of antioxidant and antibacterial activity and growth enhancer activity could be attributed to the bioactive and non digested carbohydrate content of the bulbs extracts.Â  Therefore, itÂ  could be concluded that the bulbs of eleutherine extract is potential source for â€œfeed additiveâ€ as phytobiotics as well as prebiotics.Key words: Eleutherine, Extract, Bioactive, Phytobiotics, PrebioticsÂ